Synthesis of Gold Nanoparticles Using Recovered Gold from Electronic Waste - do Nascimento, Josias do Rocio Vitor (2021)
Electronic waste contains considerable amounts of gold in its composition, especially some composting pieces like CPUs and memory cards. Recovered gold can have many uses, among those it can be an excellent alternative source for low-cost nanoparticles synthesis. Commercial chloroauric acid is the main precursor for nanoparticle synthesis, however its cost makes the process very expensive. Finding a lower cost alternative precursor is very important because it allows to economically enabling several gold nanoparticles applications. Through the hydrometallurgical method, it was possible to recover and to purify the appreciable amount of gold from old CPUs. This gold has been used to synthesize nanoparticles with a size of 198.5 nm and moderate stability. DOI:  http://dx.doi.org/10.17807/orbital.v13i2.1455